Kajian Manajemen Risiko Pekerjaan Pemasangan U-Ditch terhadap Waktu Dan Biaya - Dwi Rahayu Ningrum, Winda; Sofyan Bachmid; Watono (Universitas Nusa Putra, 2025)
The objective of this investigation was to identify the risk factors and dominant factors that affect the duration and cost of the U-Ditch installation work for the Moncongloe District drainage development project in Maros, South Sulawesi. Observation and questionnaires were implemented to conduct the investigation. Project proprietors, planners, supervisors, and implementers comprised the respondents to the questionnaire. The SPSS Version 26 program was employed to analyze the data. The data was processed in a series of phases, including validity testing, reliability testing, classical assumption testing of multiple linear regression, T test, F test, and multiple linear regression analysis. The results of this study indicated that the Standardized Coefficients Beta values of the independent variables were as follows: in the first order, variable X2 (Material) = 0.555, in the second order variable X3 (Equipment) = 0.445, in the third order variable X1 (Weather) = 0.255, in the fourth order variable X5 (Environment) = 0.254, and in the fifth order variable X4 (Labor) = 0.213. The risk factors that influence the duration and costs of the U-Ditch installation work for the Moncongloe District Drainage Development Project in Maros, South Sulawesi, as determined by these results, are as follows: materials, equipment, weather, environment, and labor. The risk factor on the independent variable X2 (Material) is the most dominant risk factor that affects the time and cost of installing U-Ditches on the Moncongloe District Drainage Development Project, Maros Regency, South Sulawesi Province, as it has the largest Standardized Coefficients Beta value of 0.555 in comparison to the Standardized Coefficients Beta value of the other independent variables.